Pengaruh Kebiasaan Bermain Game Dan Konsep Diri Terhadap Kemampuan Pemecahan Masalah Matematika di SMP NU 1 Hasyim Asy’ari Tarub - Ahmadi (Cakrawala: Jurnal Pendidikan, 2017)
The purpose of this study was to examine the effect game play habits and self-concept of the ability of solving mathematical problems. Data analysis technique used was regression analysis with two predictors. From the alculation Freg = 4.88 Ftable= 3.09 and. It concluded that Freg very significant because Freg> Ftable. This showed that there was a significant relationship between game playing habits and self-concept of the ability of solving mathematical problems. From the regression analysis of the predictors obtained t gaming habits and self-concept respectively - were at 2.29 and 2.24 and 1.98 t-table. So t-test habit of playing the game and the concept of self was greater than t-table. From the comparison between t-test and t-able, it could be concluded that there was an effect between the habit of playing the game on problem-solving ability and there was an effect between the self-concept and the ability of mathematical problem solving.